2015
DOI: 10.1249/mss.0000000000000662
|View full text |Cite
|
Sign up to set email alerts
|

Do Short Spurts of Physical Activity Benefit Cardiovascular Health? The CARDIA Study

Abstract: Background For optimal health benefits moderate to vigorous intensity physical activity (MVPA) is recommended in sustained bouts lasting ≥ 10 minutes. However, short spurts of MVPA lasting < 10 minutes are more common in everyday life. It is unclear whether short spurts of MVPA further protect against the development of hypertension and obesity in middle-aged adults beyond bouted MVPA. Methods Objectively measured physical activity was collected in the Coronary Artery Risk Development in Young Adults (CARDIA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(58 citation statements)
references
References 25 publications
1
54
0
3
Order By: Relevance
“…As regards the protective role of PA against CVD, this is not surprising, as it is widely accepted that being physically active offers protection against CVD development through several biological paths, such as reducing arterial blood pressure, reducing inflammation, balancing body weight of subjects, increasing insulin sensitivity and decreasing depression levels, and should be treated separately than traditional CVD risk factors and dietary habits. [ 7 24 25 26 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…As regards the protective role of PA against CVD, this is not surprising, as it is widely accepted that being physically active offers protection against CVD development through several biological paths, such as reducing arterial blood pressure, reducing inflammation, balancing body weight of subjects, increasing insulin sensitivity and decreasing depression levels, and should be treated separately than traditional CVD risk factors and dietary habits. [ 7 24 25 26 27 ]…”
Section: Discussionmentioning
confidence: 99%
“…Recent research using device-measured physical activity and assessing a variety of cardiometabolic health indicators indicates that bouts of MVPA of any length (ie, time duration) contribute to the health benefits associated with the accumulated total volume of physical activity. [32][33][34][35][36][37][38][39][40][41][42][43][44][45][46] Of 40 comparisons within 14 studies, 78% (31 comparisons) indicated that bouts <10 minutes long were as good or better than bouts ≥10 minutes. 1 An additional 10% (4 comparisons) reported that bouts <10 minutes long were associated with risk reduction but did not make a direct comparison with bouts ≥10 minutes.…”
Section: Schizophrenia Dmentioning
confidence: 99%
“…HIIT has been proven superior to moderate-intensity continuous aerobic exercise for improving insulin sensitivity [7] and cardiorespiratory fi tness in healthy subjects [4] and shorter bouts of exercise in contrast to a common moderate exercise program can protect against the development of arterial hypertension [8].…”
Section: Introductionmentioning
confidence: 99%